Unidades geoambientais da margem esquerda da planície aluvial do rio Ivaí-PR - Sala, Marta Gaspar (2014)
This research has as its main objective the elaboration of a geoenvironmental units map of the alluvial plain from Ivaí river (PR) left margin To the execution of this cartographic product were analyzed and mapped several elements from physical and anthropic environment (soil, geomorphology, geology, slope, hypsometry, land use and land occupation). Highlighting that in all mappings the whole alluvial plain were represented for a better visualization of the attributes that compound this landscape. However, the soil and surface and subsurface water analysis to identification a possible contamination of the ecosystem by agrichemical residua were performed only on left side, due to the extension of the whole plain and the soil e geoshapes similarity of both alluvial plain sides. The morphological and physical analysis of profiles distributed in the geoenvironmental units allowed identification of eight types of soils: Eutrophic Haplic Gleysoil cambissolic, Typical Distrophic Haplic Gleysoil, Eutrophic Haplic Gleysoil, Eutrophic Fluvic Neosols, Gley Eutrophic Fluvic Neosols, Orthic Quartzarenic Neosol, Eutrophic Red Argisoil and Medium Texture Distrophic Red Latosol (Oxisoil). Most of this soils are formed from aluvial sediments, therefore founds associated to alluvial deposits, and in general shows poorly drained, due to high hydrical availability of the plain, subjected to inundation and frequent elevation of the groundwater level. The cation-exchange capacity (CEC) and the organic matter levels showed high values in soils under natural forest cover. As for chemical analysis of water weren't found representative values of contamination. For a better understanding of the potentialities, limitations and fragilities of the study area, also were accomplished a data survey about legal legislation and the identification of environmental conservation units. Thus, the correlation of all data collected allowed the study area division in five geoenvironmental Analysis of this cartographic product evidenced that all units have potential as use, mainly agricultural with predominance of rice farming and grasslands. The mining activity, especially clay, also constitutes a potential usage in some locals. About the environmental fragilities and limitations of units are evidenced, mainly, by the generalized deforestation, by the soil characteristics, by the inundation periods, and by agrichemical contamination. Stressing that the whole study area as the whole alluvial plain of Ivaí river are part of the environmental Preservation area of Islands and floodplains of Parana River and Caiua-Ilha Grande biodiversity corridor, that are included in the Ilha Grande National. However, it appears that the area is a form of occupation, mainly focused on agriculture without a commitment to preserve and reconstruct the remaining natural forest or even use them in a sustainable manner..